Preparation and Structural Studies of new Metal Complexes with 2-N(4- N,N- dimethyl benzyliden ) 5 - (p- methoxy phenyl)- 1,3,4- thiodiazole - Abraheim, S. K.; Bakir, Sh. R.; Alias, M. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A new Schiff base, 2-N( 4- N,N â€“ dimethyl benzyliden )5 â€“ (p- methoxy phenyl) â€“ 1,3,4- thiodiazol ,and their metal complexes Cu (Î ) ,Ni (Î ),         Fe (III) , Pd (Î ) , Pt (IV) , Zn(Î ) ,V(IV) and Co (Î ) , were synthesized. The prepared complexes were identified and their structural geometries were suggested by using flam atomic absorption technique , FT-IR and Uv-Vis spectroscopy, in addition to magnetic susceptibility and conductivity measurements. The study of the nature of the complexes formed in ethanol solution , following the mole ratio method , gave results which were compared successfully with those obtained from the isolated solid state studied. Structural geometries of compounds were also suggested in gas phase by using theoretical treatments , using HyperChem-6 program for the molecular mechanics and semi- empirical calculations. The heat of formation (âˆ†HÆ’Â°) and binding energy (âˆ†Eb) for the free ligand and their metal complexes were calculated by PM3 and AMBER methods, PM3 was used to evaluate the vibration spectra of schiff base and to compare the theoretically calculated wave numbers with exprimental values by using 2- amino- 5 (p- methoxy phenyl)-1,3,4- thiodiazole as authentic compound. The theoretically obtained frequencies agreed calculation helped to assign unambiguously the most diagnostic bands.